SOCIAL WORKERS TRAINING IN CONTINUING EDUCATION SYSTEM - Spirina, Tеtiana; Liakh, Tеtiana (The Modern Higher Education Review, 2020)
The development of a continuing education system is a strategic task of reforming all education systems that consistently define their national-specific characteristics, while at the same time focusing on basic educational principles. The rapid changes in current development of society, related to the humanization of education, the high demands on each member of society, both individual and professional, and make the relevance of adult education as an integral part of continuing education and expanding research in this field. Particularly valuable are studies on the lifelong learning of social workers who are mediators between the state and society, agents of change and improvement of social and educational policies. Recognizing the competence approach in education and training of social workers, which should be reflected in updating the content of education in response to social transformations, engages the creation of conditions for the development of lifelong education in the field of professional activity of a social worker as a generalized condition for the ability to act effectively in a particular professional situation. The article deals with the problem of professionals training in the social field in continuing education system, which provides the professional development of adults, in particular social workers. The development of a continuing education system is a strategic task of reforming all education systems that consistently define their national-specific characteristics, while at the same time focusing on basic educational principles.